O sabor do saber: divulgação científica em interação no YouTube - Reale, Manuella Vieira (2018)
This research seeks to understand which are the different enunciative strategies and the regimes of meaning and interaction of scientific communication brazilian channels on online videos - especially on YouTube s platform - as a way to cultivate the taste for science. Therefore, we aim: investigate the constructed senses and ways of presence of scientific communication destinators in the selected digital environment; observe and question the scientific communication terminology; identify enunciation marks that indicate doings shaped by metadestinator YouTube; discuss what leads a certain statement to be credible; debate the scientific communication as an approximation between scientific field and common sense. lt is recognized the relevance of scientific field in contemporary society and the role of scientific communication in dissemination of complex science. Hypotheses to be tested are: YouTube enables multiplicate audiovisual productions about scientific knowledge; scientific communication channels make the taste for science an object of value in the approximation between scientific knowledge and common sense; interactions promoted in this platform provide feedback on the part of the destinee, revealing their simulacra. The object of study consists in channels with scientific content, whose posting is regular, recent and original. A mapping is accomplished of the productions by search and data survey, resulting in an overview of current brazilian productions whose division was made in four categories relating degree of audiovisual production and formal specialization in science. They are: Beginner, Professional Producer, Certificated Specialist and lnitiated. The corpus channels, chosen respectively from each category, are: Alimente o Cerebro, Manual do Mundo, Canal do Pirula and Nerdologia. The theoretical current of French semiotics of Algirdas J. Greimas and his followers, based on the generative course of meaning, will ground the analysis of enunciation in each syncretic text, as well as the meaning and interaction regimes according to Eric Landowski. Regarding the science notion, the main authors are Thomas Kuhn and Edgar Morin and, to discuss scientific communication definition, Wilson Bueno, Carlos Vogt and Bruce Lewestein. ln meaning and interaction regimes, it is possible to see how destinators use strategic narratives to impel the construction of meaning along the destinee in order to accentuate the taste for science as an object of value